Polyacrylamide-based gel electrolyte as well as preparation process and application thereof

By introducing polyacrylamide gel electrolyte into lithium metal batteries, free radical polymerization is initiated through heating, and a fast lithium ion transmission channel is constructed, which solves the problem of lithium ion transmission kinetics limitation in lithium metal batteries and improves the ion conductivity and discharge capacity of the battery.

CN120357024APending Publication Date: 2025-07-22HEYUAN LICHUANG (SUZHOU) NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510527003.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

Lithium ion transport kinetic limitations in existing lithium metal batteries lead to lower ion conductivity and discharge specific capacity, as well as poor rate performance.

Method used

The polyacrylamide gel electrolyte is used to heat N-(2,2,2-trifluoroethyl)acrylamide, free radical initiator and organic electrolyte at 55~80°C to initiate radical polymerization to construct a fast lithium ion transmission channel.

Benefits of technology

The ionic conductivity of gel electrolyte is improved and the discharge capacity and rate performance of lithium metal batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120357024A_ABST
    Figure CN120357024A_ABST
Patent Text Reader

Abstract

The invention relates to a polyacrylamide-based gel electrolyte and a preparation method and application thereof, the gel electrolyte is obtained by heating a gel electrolyte precursor solution containing N-(2, 2, 2-trifluoroethyl) acrylamide, a free radical initiator and an organic electrolyte to initiate free radical polymerization; the gel electrolyte is applied to the lithium metal battery. According to the polyacrylamide-based gel electrolyte as well as the preparation method and the application thereof, the monomer N-(2, 2, 2-trifluoroethyl) acrylamide containing an acrylamide group is introduced into the gel electrolyte, and because the amide group has very strong electronegativity and interacts with lithium ions, a rapid lithium ion transmission channel is constructed at an interface of a polymer and a solvent, so that the lithium ion conductivity of the gel electrolyte is improved, and the performance of the gel electrolyte is improved. When the gel electrolyte is applied to a lithium metal battery, the polarization phenomenon of the battery in the charging and discharging process is reduced, the discharging capacity of the battery is improved, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and specifically relates to a polyacrylamide-based gel electrolyte, its preparation process, and its application in lithium metal batteries. Background Art

[0002] Due to the high theoretical specific capacity of the lithium metal anode (3860 mAh g -1 ), and the lowest electrochemical potential (3.04 V compared to the standard hydrogen electrode), it is considered an ideal anode material for next-generation batteries. However, using a lithium metal anode faces the risk of lithium dendrites penetrating the electrolyte. Traditional organic electrolytes cannot resist the growth of lithium dendrites and even pose safety hazards such as combustion and explosion, thus hindering the development of lithium metal batteries.

[0003] By adding organic small molecule monomers to the electrolyte and then initiating chemical cross-linking under heating or light conditions, a gel electrolyte can be in-situ polymerized. Using a gel electrolyte instead of an electrolyte can effectively solve the safety problems existing in lithium metal batteries. Moreover, the gel electrolyte also has the advantage of good interfacial compatibility with the electrode, making it have good application prospects in the application of solid-state lithium metal batteries.

[0004] Chinese Patent CN116154280A discloses a method for improving the cycling performance of lithium metal batteries by introducing one or more functional additives such as ethyl 4-dihydropyrimidin-2-ylcarbamate, 2,2,3,3,3-pentafluoropropyl acrylate, or pentaerythritol tetraacrylate into the gel electrolyte.

[0005] Chinese Patent CN117558972B discloses a method for improving the mechanical properties of the electrolyte and the interfacial compatibility between the electrode and the electrolyte by introducing ionic liquids and inorganic fillers into the gel electrolyte.

[0006] Although the above modification methods have improved the cycling performance of lithium metal batteries to a certain extent, the lithium ion transport kinetics is still limited, resulting in low ionic conductivity, low discharge specific capacity, and poor rate performance.

[0007] To solve the above problems, the present invention provides a polyacrylamide-based gel electrolyte, its preparation process, and its application in lithium metal batteries. Summary of the Invention

[0008] Objective of the Invention: To overcome the above deficiencies, the objective of the present invention is to provide a polyacrylamide-based gel electrolyte, its preparation process and application. By utilizing the strong electronegativity of the amide group, which can interact with lithium ions, a fast lithium ion transport channel is constructed at the polymer-solvent interface, thereby effectively enhancing the ionic conductivity of the gel electrolyte for application in lithium metal batteries.

[0009] The objective of the present invention is achieved through the following technical solutions: A polyacrylamide-based gel electrolyte, wherein the gel electrolyte is obtained by heating and initiating free radical polymerization of a gel electrolyte precursor solution containing N-(2,2,2-trifluoroethyl)acrylamide, a free radical initiator, and an organic electrolyte at 55 - 80 °C.

[0010] Furthermore, for the above polyacrylamide-based gel electrolyte, the polymer of the gel electrolyte is a homopolymer of the monomer N-(2,2,2-trifluoroethyl)acrylamide.

[0011] Furthermore, for the above polyacrylamide-based gel electrolyte, the proportion of N-(2,2,2-trifluoroethyl)acrylamide in the gel electrolyte precursor solution is 10 - 20 wt%, the proportion of the free radical initiator is 0.2 - 2 wt%, and the proportion of the organic electrolyte is 60 - 95 wt%.

[0012] Preferably, the proportion of N-(2,2,2-trifluoroethyl)acrylamide in the gel electrolyte precursor solution is 15 wt%, the proportion of the free radical initiator is 0.5 wt%, and the proportion of the organic electrolyte is 85 wt%.

[0013] Furthermore, for the above polyacrylamide-based gel electrolyte, the free radical initiator is 2,2-azobis(isobutyronitrile).

[0014] Furthermore, for the above polyacrylamide-based gel electrolyte, the organic electrolyte is an electrolyte commonly used in the field of lithium metal batteries, including but not limited to one selected from 1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol%, 1M LiPF6 in DEC:EC = 1:1 Vol%, 1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol% with 1% VC.

[0015] Furthermore, for the above polyacrylamide-based gel electrolyte, the gel electrolyte precursor solution initiates free radical polymerization at 60 °C.

[0016] The present invention also relates to the preparation process of the above polyacrylamide-based gel electrolyte, which includes the following steps: S1: Uniformly mix N-(2,2,2-trifluoroethyl)acrylamide, a radical initiator, and an organic electrolyte to prepare a gel electrolyte precursor solution; S2: Inject the above gel electrolyte precursor solution into a battery for assembly, and initiate radical polymerization by heating at 55-80 °C to obtain a gel electrolyte.

[0017] Preferably, both S1 and S2 are carried out in a glove box filled with argon with H2O < 0.1 ppm and O2 < 0.1 ppm.

[0018] Preferably, in S2, when assembling the battery, a PP separator is used to separate the positive electrode and the negative electrode, and the gel electrolyte precursor solution is injected on both sides of the PP separator to infiltrate the interface between the positive electrode and the negative electrode.

[0019] Preferably, in S2, the temperature of radical-initiated polymerization is 60 °C and the time of radical-initiated polymerization is 1 h.

[0020] Furthermore, for the preparation process of the above polyacrylamide-based gel electrolyte, the synthesis method of N-(2,2,2-trifluoroethyl)acrylamide is as follows: First, add a mixture of 10 mL of triethylamine and 40 mL of dichloromethane to a flask filled with N2, then add 20 mmol of 2,2,2-trifluoroethylamine and stir in an ice-water bath. At the same time, dissolve 20 mmol of acryloyl chloride in 20 mL of dichloromethane and add it dropwise to the flask within 3 h; after stirring for 12 h, wash with deionized water, and separate and extract to collect the organic phase and dry it with anhydrous sodium sulfate; after removing the solvent by vacuum distillation, obtain a liquid crude product; preliminarily purify the liquid crude product by silica gel column chromatography to obtain a light yellow liquid product, and further purify it by recrystallization to obtain a white solid powder, thus preparing N-(2,2,2-trifluoroethyl)acrylamide.

[0021] Preferably, the liquid crude product is preliminarily purified by silica gel column chromatography, and the eluent is petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate is 3:1.

[0022] The present invention also relates to the application of the above polyacrylamide-based gel electrolyte. When it is applied to a lithium metal battery, it can reduce the polarization phenomenon during the charge and discharge process of the battery, improve the discharge capacity of the battery, and improve the rate performance of the battery.

[0023] Furthermore, for the application of the above polyacrylamide-based gel electrolyte, the electrolyte of the lithium metal battery is a polyacrylamide-based gel electrolyte, the negative electrode is a lithium metal foil, and the positive electrode is an NCM811 electrode sheet.

[0024] Preferably, the negative electrode is a lithium metal foil with a thickness of 50 μm.

[0025] Preferably, the NCM811 electrode is prepared as follows: The active material NCM811 powder, acetylene black, and PVDF are mixed in a solvent NMP at a mass ratio of 8:1:1 and stirred overnight, then coated on an aluminum foil and dried in a vacuum drying oven at 80 °C for 12 h. The areal loading of the NCM811 positive electrode is about 2 mg cm⁻².

[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The polyacrylamide-based gel electrolyte disclosed in the present invention introduces a monomer containing an acrylamide group into the gel electrolyte. Since the acrylamide group has a strong electronegativity, it can promote the rapid transport of lithium ions, thereby enhancing the ionic conductivity of the gel electrolyte; (2) The preparation process of the polyacrylamide-based gel electrolyte disclosed in the present invention has a simple preparation method and has a wide range of application scenarios in the field of lithium metal batteries; (3) The application of the polyacrylamide-based gel electrolyte disclosed in the present invention applies the prepared polyacrylamide-based gel electrolyte to a lithium metal battery, improving the discharge specific capacity of the lithium metal battery and improving the rate performance of the battery. Description of the Drawings

[0027] Figure 1 1H NMR spectrum of N-(2,2,2-trifluoroethyl)acrylamide prepared in the polyacrylamide-based gel electrolyte of the present invention; Figure 2 Digital photos of the gel electrolyte precursor solutions in Examples 1 and 2 of the present invention after being kept at 60 °C for 1 h; Figure 3 Ionic conductivity graphs of the gel electrolyte in Example 2 and the electrolyte in Comparative Example 1 of the present invention at 30 °C; Figure 4 First charge-discharge curve of the long cycle test of the battery in Example 2 of the present invention; Figure 5 Graph of the long cycle test of the battery in Example 2 of the present invention; Figure 6 Rate performance graph of the battery in Example 2 of the present invention. Detailed Description of the Invention

[0028] Next, Examples 1, 2, 3, and Comparative Example 1 will be combined with the attached Figure 1 , 2, 3, 4, 5, 6 and specific experimental data are used to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the protection scope of the present invention.

[0029] Unless otherwise specified, the reagents, methods and equipment used in the embodiments of the present invention are conventional reagents, methods and equipment in the technical field.

[0030] The reagents required for the experiments in the embodiments of the present invention are as shown in Table 1 below: Table 1 List of Reagents Required for Experiments Reagent Name Chemical Formula / Abbreviation Purity Manufacturer Electrolyte <![CDATA[1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol% with 1% VC]]> Analytical Reagent Grade Duoduo Chemical Reagents Acryloyl Chloride <![CDATA[C3H3ClO]]> 96% Aladdin Biochemical Technology 2,2,2-Trifluoroethylamine <![CDATA[C2H4F3N]]> 99.9% Macklin Reagents 2,2'-Azobis(2-methylpropionitrile) AIBN 98% Energy Chemical Dichloromethane <![CDATA[CH2Cl2]]> 99.9% J&K Scientific Triethylamine <![CDATA[C6H 15 N]]> Analytical Reagent Grade HuShi Petroleum Ether PE 60 ~ 90 Kelong Chemicals Ethyl Acetate EA 99.5% Kelong Chemicals Among them, the N-(2,2,2-trifluoroethyl)acrylamide is self-made, and its structural formula is as follows: The synthesis method of the N-(2,2,2-trifluoroethyl)acrylamide is as follows: First, a mixture of 10 mL of triethylamine and 40 mL of dichloromethane is added to a three-necked round-bottom flask filled with N2, and then 20 mmol of 2,2,2-trifluoroethylamine is added and stirred in an ice-water bath. At the same time, 20 mmol of acryloyl chloride is dissolved in 20 mL of dichloromethane and added dropwise to the mixture in the three-necked round-bottom flask within 3 h. After stirring for 12 h, it is washed with deionized water, and the organic phase is collected by liquid separation and extraction, and dried with anhydrous sodium sulfate. After removing the solvent by vacuum distillation, a liquid crude product is obtained. The liquid crude product is preliminarily purified by silica gel column chromatography (the volume ratio of petroleum ether to ethyl acetate in the eluent is 3:1) to obtain a light yellow liquid product. Further purification by recrystallization gives a white solid powder, which is N-(2,2,2-trifluoroethyl)acrylamide.

[0031] Figure 1 This is the 1H NMR spectrum of the N-(2,2,2-trifluoroethyl)acrylamide prepared in the present invention, and the peak positions are corrected using deuterated dimethyl sulfoxide (DMSO).

[0032] The following Examples 1, 2, 3 and Comparative Example 1 provide an electrolyte and its application in a lithium metal battery.

[0033] Example 1 Example 1 uses a gel electrolyte, and its preparation includes the following steps: S1: Dissolve 0.1 g of N-(2,2,2-trifluoroethyl)acrylamide and 0.005 g of AIBN in 0.9 g of electrolyte solution, and shake well for 5 min until evenly mixed to prepare a gel electrolyte precursor solution; S2: Inject 15 μL of the above gel electrolyte precursor solution into a 2032-type button cell. Use a PP separator to separate the positive and negative electrodes. Then, keep the obtained button cell at 60 °C for 1 h to initiate polymerization. The proportion of monomer N-(2,2,2-trifluoroethyl)acrylamide in the gel electrolyte is 10 wt%.

[0034] The above steps are all carried out in a glove box filled with argon with H2O < 0.1 ppm and O2 < 0.1 ppm.

[0035] Example 2 Example 2 uses a gel electrolyte, and its preparation includes the following steps: S1: Dissolve 0.15 g of N-(2,2,2-trifluoroethyl)acrylamide and 0.005 g of AIBN in 0.85 g of electrolyte solution, and shake well for 5 min until evenly mixed to prepare a gel electrolyte precursor solution; S2: Inject 15 μL of the above gel electrolyte precursor solution into a 2032-type button cell. Use a PP separator to separate the positive and negative electrodes. Then, keep the obtained button cell at 60 °C for 1 h to initiate polymerization. The proportion of monomer N-(2,2,2-trifluoroethyl)acrylamide in the gel electrolyte is 15 wt%.

[0036] The above steps are all carried out in a glove box filled with argon with H2O < 0.1 ppm and O2 < 0.1 ppm.

[0037] Example 3 Example 3 uses a gel electrolyte, and its preparation includes the following steps: S1: Dissolve 0.2 g of N-(2,2,2-trifluoroethyl)acrylamide and 0.005 g of AIBN in 0.8 g of electrolyte solution, and shake well for 5 min until evenly mixed to prepare a gel electrolyte precursor solution; S2: Inject 15 μL of the above gel electrolyte precursor solution into a 2032-type button cell. Use a PP separator to separate the positive and negative electrodes. Then, keep the obtained button cell at 60 °C for 1 h to initiate polymerization. The proportion of monomer N-(2,2,2-trifluoroethyl)acrylamide in the gel electrolyte is 20 wt%.

[0038] The above steps are all carried out in a glove box filled with argon with H2O < 0.1 ppm and O2 < 0.1 ppm.

[0039] Comparative Example 1 In Comparative Example 1, a commercially available electrolyte was used, with the composition of 1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol% with 1% VC. When assembling the battery, 15 μL of the above electrolyte was injected into a CR2032 coin cell, and a PP separator was used to separate the positive and negative electrodes. The above steps were all carried out in a glove box filled with argon with H2O < 0.1 ppm and O2 < 0.1 ppm.

[0040] Effect Verification Perform performance tests on Example 1, Example 2, Example 3 and Comparative Example 1, and the measurement results are as Figure 2 、 3 shown in Figures 4, 5, and 6.

[0041] Figure 2 are digital photos of the gel electrolyte precursor solutions in Example 1 and Example 2 after being kept at 60 °C for 1 h. As Figure 2 shown, when the proportion of N-(2,2,2-trifluoroethyl)acrylamide is 10%, the gel electrolyte precursor solution cannot be completely polymerized. When the proportion of N-(2,2,2-trifluoroethyl)acrylamide reaches 15%, the gel electrolyte precursor solution can be completely polymerized and cured into a gel.

[0042] Test the ionic conductivity of the gel electrolyte in Example 2 and the electrolyte in Comparative Example 1 at 30 °C through the electrochemical impedance spectroscopy (EIS) of the Zahner potentiostat-galvanostat electrochemical workstation. From Figure 3 it can be seen that the conductivity of the gel electrolyte in Example 2 is 6.08 mS cm -1 , and the ionic conductivity of the electrolyte in Comparative Example 1 is 6.32 mS cm -1 . The gel electrolyte of Example 2 is comparable to the electrolyte of Comparative Example 1 and has a high ionic conductivity.

[0043] Figure 4 is the first charge-discharge curve of the NCM811 / Li full cell assembled in Example 2 during the long-term cycling test at a test temperature of 30 °C and a current density of 0.1C. From Figure 4 it can be seen that the discharge specific capacity of the NCM811 / Li full cell assembled in Example 2 is as high as 195.55 mAh g-1, and the first-cycle Coulombic efficiency is 85.49%.

[0044] Figure 5 is the graph of the long-term cycling performance test of the NCM811 / Li full cell assembled in Example 2 at a test temperature of 30 °C and a current density of 0.5C. From Figure 5It can be seen that after 50 stable cycles of the NCM811 / Li full battery assembled in Example 2, there is still a high capacity retention of 160.53 mAh g -1 .

[0045] Figure 6 Fig. Figure 6 is the rate performance graph of the NCM811 / Li full battery assembled in Example 2 at a test temperature of 30°C. It can be seen from Figure 6 that the NCM811 / Li full battery assembled in Example 2 can be tested at a high current density, and even at 10C, there is still a capacity of 56.75 mAh g -1 .

[0046] In summary, the gel electrolyte prepared by the technical solution of the present invention has good ionic conductivity. When it is applied to a lithium metal battery, it effectively reduces the polarization phenomenon during the charge and discharge process of the battery, improves the discharge capacity of the battery, and improves the rate performance of the battery. It has a wide range of application scenarios in the field of lithium metal batteries.

[0047] There are many specific application ways of the present invention, and the above is only the preferred implementation manner of the present invention. It should be noted that the above embodiments are only used to illustrate the present invention, and do not limit the protection scope of the present invention. For those of ordinary skill in the art in this technical field, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.

Claims

1. A polyacrylamide-based gel electrolyte, characterized in that, The gel electrolyte is obtained by initiating radical polymerization of a gel electrolyte precursor solution containing N-(2,2,2-trifluoroethyl)acrylamide, a radical initiator, and an organic electrolyte solution by heating at 55-80 °C.

2. The polyacrylamide-based gel electrolyte according to claim 1, wherein The polymer of the gel electrolyte is a homopolymer of the monomer N-(2,2,2-trifluoroethyl)acrylamide.

3. The polyacrylamide-based gel electrolyte according to claim 1, wherein In the gel electrolyte precursor solution, the proportion of N-(2,2,2-trifluoroethyl)acrylamide is 10-20 wt%, the proportion of the radical initiator is 0.2-2 wt%, and the proportion of the organic electrolyte solution is 60-95 wt%.

4. The polyacrylamide-based gel electrolyte according to claim 1, wherein The radical initiator is 2,2'-azobis(isobutyronitrile).

5. The polyacrylamide-based gel electrolyte according to claim 1, characterized in that, The organic electrolyte solution includes but is not limited to one selected from 1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol%, 1M LiPF6 in DEC:EC = 1:1 Vol%, 1M LiPF6 in DMC:EC:EMC = 1:1:1 Vol% with 1% VC.

6. The polyacrylamide-based gel electrolyte according to claim 1, wherein The gel electrolyte precursor solution initiates radical polymerization at 60 °C.

7. The preparation method of the polyacrylamide-based gel electrolyte according to any one of claims 1 to 6, characterized in that, It includes the following steps: S1: Uniformly mix N-(2,2,2-trifluoroethyl)acrylamide, a radical initiator, and an organic electrolyte solution to prepare a gel electrolyte precursor solution; S2: Heat the above gel electrolyte precursor solution at 55-80 °C to initiate radical polymerization to obtain a gel electrolyte.

8. The preparation method of the polyacrylamide-based gel electrolyte according to claim 7, characterized in that, The synthesis method of N-(2,2,2-trifluoroethyl)acrylamide is as follows: First, add a mixture of 10 mL of triethylamine and 40 mL of dichloromethane to a flask filled with N2, then add 20 mmol of 2,2,2-trifluoroethylamine and stir in an ice-water bath. At the same time, dissolve 20 mmol of acryloyl chloride in 20 mL of dichloromethane and add it dropwise to the flask within 3 h; after stirring for 12 h, wash with deionized water, and separate and extract to collect the organic phase and dry it with anhydrous sodium sulfate; after removing the solvent by vacuum distillation, obtain a liquid crude product; preliminarily purify the liquid crude product by silica gel column chromatography to obtain a light yellow liquid product, and further purify it by recrystallization to obtain a white solid powder, thus preparing N-(2,2,2-trifluoroethyl)acrylamide.

9. Use of the polyacrylamide-based gel electrolyte according to any one of claims 1 to 6, characterized in that, The gel electrolyte is applied to a lithium metal battery.

10. The application of the polyacrylamide-based gel electrolyte according to claim 9, characterized in that, The electrolyte of the lithium metal battery is a gel electrolyte, the negative electrode of the lithium metal battery is a metal lithium foil, and the positive electrode is an NCM811 electrode sheet.

Citation Information

Patent Citations

  • Gel electrolyte of lithium battery and application of gel electrolyte

    CN116154280A

  • An inorganic composite gel polymer electrolyte and its preparation method and application

    CN117558972B